2021
DOI: 10.1021/acsami.1c05412
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Distribution of Pt16(C4O4SH5)26 Clusters in ZIF-67 for Efficient Hydrogen Generation and Oxygen Reduction

Abstract: In recent years, based on the high catalytic activities of metal nanoclusters (MNCs) and the unique porous structure of metal–organic frameworks (MOFs), much work has focused on MOF-confined small MNCs for catalysis applications. However, the commonly used “ship-in-boat” approach is unfeasible for precisely controlling the size and composition of the formed MNCs and meanwhile often causes structural distortion/degradation. On the other hand, the “bottle-around-ship” method usually has the disadvantages that MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…[30] Chen and colleagues encapsulated monodisperse Pt 16 (C 4 O 4 SH 5 ) 26 NCs in ZIF-67 and removed ligands to obtain Pt@ZIF-67. [31] The prepared catalyst exhibited high catalytic activity for the hydrolysis of ammonia borane that was superior to that of catalysts previously reported. In recent years, Cu catalysts have been widely used in the field of catalysis and show good performance.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…[30] Chen and colleagues encapsulated monodisperse Pt 16 (C 4 O 4 SH 5 ) 26 NCs in ZIF-67 and removed ligands to obtain Pt@ZIF-67. [31] The prepared catalyst exhibited high catalytic activity for the hydrolysis of ammonia borane that was superior to that of catalysts previously reported. In recent years, Cu catalysts have been widely used in the field of catalysis and show good performance.…”
Section: Introductionmentioning
confidence: 77%
“…Li and co‐workers designed Pd 3 Cl NCs for the Suzuki‐Miyaura C−C cross‐coupling, which shows excellent catalytic activity [30] . Chen and colleagues encapsulated monodisperse Pt 16 (C 4 O 4 SH 5 ) 26 NCs in ZIF‐67 and removed ligands to obtain Pt@ZIF‐67 [31] . The prepared catalyst exhibited high catalytic activity for the hydrolysis of ammonia borane that was superior to that of catalysts previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…1–6 The sluggish kinetics of catalysts in the oxygen reduction reaction (ORR), oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are known to govern their performance in energy utilization and power output. 7–14 Generally, platinum (Pt) on carbon materials has been widely used for ORR, 15–17 OER, 18–20 HER, 21–23 and hydrogen storage. 24–29 However, these catalysts require relatively large surface area, high electrical conductivity of carbon materials, and high loading density and uniform dispersion of platinum nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…[16] It is hard to achieve excellent electrochemical performance with these catalysts because that the kinetics of OER and oxygen reduction reaction (ORR) are slow. [17][18][19][20] Researches have shown that carbon materials have great potential for developing high-performance, low-cost catalysts by co-doping metallic and non-metallic heteroatoms. [21][22][23][24] Notably, metal(Co)À NÀ C has emerged as a promising candidate for researchers due to its low cost and high catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…So far, researchers devote themselves to explore non‐noble metal oxides, non‐noble metal heteroatoms doped with carbon and so on to improve their catalytic performance [16] . It is hard to achieve excellent electrochemical performance with these catalysts because that the kinetics of OER and oxygen reduction reaction (ORR) are slow [17–20] . Researches have shown that carbon materials have great potential for developing high‐performance, low‐cost catalysts by co‐doping metallic and non‐metallic heteroatoms [21–24] .…”
Section: Introductionmentioning
confidence: 99%